First-Line Treatment in EGFR Mutant Non-Small Cell Lung Cancer: Is There a Best Option? - Bulbul, Ajaz; Husain, Hatim (Frontiers in Oncology, 2018)
First-generation or second-generation EGFR tyrosine kinase inhibitors are currently the standard of care for the first-line management of NSCLC patients with activating mutations within the kinase domain of the epidermal growth factor receptor gene1,2. Resistance to targeted therapy can develop after 9–11 months on first or second generation anti-EGFR TKI therapy3-8. Osimertinib was developed to target the EGFR T790M clone, which is the most common dominant second site resistance mutation after first or second-generation inhibitors. Osimertinib received full FDA approval for the second line treatment of advanced NSCLC based on a phase III study comparing the compound to chemotherapy. Additionally, recent data demonstrates an important impact for osimertinib in the first-line space based on results comparing the compound to first line first generation erlotinib or gefitinib therapy.